2015
DOI: 10.1103/physreve.92.052112
|View full text |Cite
|
Sign up to set email alerts
|

Correlation function for generalized Pólya urns: Finite-size scaling analysis

Abstract: We describe a universality class for the transitions of a generalized Pólya urn by studying the asymptotic behavior of the normalized correlation function C(t) using finite-size scaling analysis. X(1), X(2), · · · are the successive additions of a red (blue) ball (X(t) = 1 (0)) at stage t and C(t) ≡ Cov(X(1), X(t + 1))/Var(X(1)). Furthermore, z(t) = t s=1 X(s)/t represents the successive proportions of red balls in an urn to which, at the t + 1-th stage, a red ball is added (X(t + 1) = 1) with probability q(z(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Another possible avenue to explore is the recent study of random walks with extreme value memory discussed in [38]. Finally, we note a strong parallel with ideas emerging from studies of other generalised Pólya urn processes based on a scaling analysis of the correlation function relating the first and last step [39]. …”
mentioning
confidence: 63%
“…Another possible avenue to explore is the recent study of random walks with extreme value memory discussed in [38]. Finally, we note a strong parallel with ideas emerging from studies of other generalised Pólya urn processes based on a scaling analysis of the correlation function relating the first and last step [39]. …”
mentioning
confidence: 63%
“…As the interaction is strong, the statistical mechanical approach is promising [13,14]. One example is the phase transition caused by the information cascade [15,16]. Information cascade is the tendency to choose the majority choice even if one thinks the minority option is correct or optimal [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that as the difficulty of the question increases, the number of stable states changes. The change in the number of the stable states induces a nonequilibrium discontinuous phase transition in the infinite population limit [16]. The performance of humans is greatly improved by social learning, and this is called the collective intelligence effect [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…On the phase boundary between the one-peak and two-peaks phase, the result for a generalized Pólya urn process suggests the following asymptotic behavior [27].…”
Section: Estimator For L and Var(z)mentioning
confidence: 99%
“…The phase transition of the voting models was detected by considering that the normalized correlation function C(t) between the first voter's choice and (t +1)-th voter's choice plays a key role [26], [27]. The function is defined as the covariance divided by the variance of the first voter's choice.…”
Section: Estimator For L and Var(z)mentioning
confidence: 99%